2013
DOI: 10.1371/journal.pone.0063246
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Mandatory Bovine Abortion Notification System in France Using Unilist Capture-Recapture Approach

Abstract: The mandatory bovine abortion notification system in France aims to detect as soon as possible any resurgence of bovine brucellosis. However, under-reporting seems to be a major limitation of this system. We used a unilist capture-recapture approach to assess the sensitivity, i.e. the proportion of farmers who reported at least one abortion among those who detected such events, and representativeness of the system during 2006–2011. We implemented a zero-inflated Poisson model to estimate the proportion of farm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
1
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 24 publications
1
37
1
1
Order By: Relevance
“…This study confirmed the influence of the production type and herd size on the probability for a farmer to report abortion (Bronner et al, 2013). Indeed, beef cattle farmers face difficulties in detecting and catching aborting females at pasture for a serological analysis (Bronner et al, 2014).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…This study confirmed the influence of the production type and herd size on the probability for a farmer to report abortion (Bronner et al, 2013). Indeed, beef cattle farmers face difficulties in detecting and catching aborting females at pasture for a serological analysis (Bronner et al, 2014).…”
Section: Discussionsupporting
confidence: 76%
“…Besides, the proportion of notifying farmers (i.e. the ratio of the number of farmers who reported at least one abortion to the total number of farmers) and the sensitivity of the surveillance system were highly influenced by the occurrence of the bluetongue virus serotype 8 (BTV-8) in 2007/2008 in France, due to an increase in abortions occurrence and to an increase in farmers' and veterinarians' awareness of the need to detect the disease (Bronner et al, 2013). However, we wondered whether this influence was specific to BTV-8, or would also exist if other abortive diseases occurred or were monitored.…”
Section: Mixedmentioning
confidence: 99%
“…In epidemiology, depending on the number of data sources, two capture-recapture approaches can be used: multilist and unilist approaches (Vergne et al, 2015). While multilist capture-recapture methods are relevant when infected units can be detected by several surveillance systems or components, unilist methods focus on the frequency of detection of infected units by a single source ("one list") of observations (Bronner et al, 2013;Chao et al, 2001;Del Rio Vilas and Böhning, 2008;Vergne et al, 2012). In this study, a unilist capture-recapture approach was used with the detection source being the surveillance component targeting the breeding stock.…”
Section: Capture-recapture Methodsmentioning
confidence: 99%
“…Elbers et al (26) describe the early detection of the first BT virus 8-(BTV-8-) infected sheep flocks in the Netherlands by farmers and veterinary practitioners on the basis of an unusual clinical syndrome. Another use of syndromic surveillance is the potential for the notification of abortions in livestock to provide early warning of RVF (27). The use of a continuous indicator (milk yield) for early detection of VBDs, using a scan statistic to detect clusters of low milk production, has been evaluated and the main limitation was found to be its low specificity (28).…”
Section: Syndromic Surveillancementioning
confidence: 99%